Kontrol Glikemik terhadap Kadar Profil Lipid pada Pasien DM Tipe 2 - Lestari, Wuni Sri; Fitriana, Eka; Karwiti, Witi; Unjani, Sri (Journal of Telenursing (JOTING), 2023)
This study analyzes the relationship between glycemic control and lipid profile levels in type 2 DM patients. The research method used in this research is a cross-sectional study. The statistical test used is chi-square. The research showed that of the 50 respondents suffering from type 2 DM, the most significant percentage were women (70%) and in the adult age category (68%). There is a relationship between cholesterol levels (p = 0.010) and LDL (p = 0.012) with glycemic control (HbA1C). ) not related. The research conclusion is that glycemic control (HbA1C) is related to cholesterol and LDL levels. Keywords: Diabetes Mellitus, Type 2 DM, Glycemic Control, Lipid Profile